Histological and Histochemical Studies on the Alveolar Tissue of Gaddi Sheep - Pathak, Virender (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on alveolar tissue of lungs of Gaddi Sheep. Tissues were collected from 30 healthy adult of both sexes. The tissues were processed for micrometrical and histological studies. The study revealed that average size of alveolar duct was 141 ± 7.86 μm. The alveolar duct was lined with simple squamous (Pneumocyte-I) and cuboidal epithelium (Pneumocyte-II). The average diameter of alveolar sac was 270.72 ± 10.12 μm in Gaddi sheep. Alveolar sac was surrounded by thinly woven network of reticular and elastic fibers. Two predominant types of epithelial cells were observed in alveoli. Thin membranous flat squamous cells were called Pneumocyte-I and cuboidal cells as Pneumocyte-II. The average height of Pneumocyte-I cells was 4.02 ± 0.13 μm and of Pneumocytes type-II was 7.45 ± 0.12 μm. Pneumocyte-II stained moderately for carbohydrates and acidic mucopolysaccharides. The basement membrane was strongly positive for carbohydrates and mildly positive for acidic mucopolysaccharides. The average thickness of the blood air barrier was 8.04 ± 0.15μm in Gaddi sheep.